Novel Fig-Associated Viroid-Like RNAs Containing Hammerhead Ribozymes in Both Polarity Strands Identified by High-Throughput Sequencing - Olmedo-Velarde, Alejandro; Navarro, Beatriz; Hu, John S.; Melzer, Michael J.; Di Serio, Francesco (Frontiers in Microbiology, 2020)
Based on high-throughput sequencing (HTS) data, the existence of viroid-like RNAs associated with fig trees grown in the Hawaiian Islands has been predicted. One of these RNAs has been characterized as a circular RNA ranging in size from 357 to 360 nucleotides. Structural and biochemical features of this RNA, tentatively named fig hammerhead viroid-like RNA (FHVd-LR), markedly resemble those previously reported for several viroids and viroid-like satellite RNAs (Vd-LsatRNAs), which are non-protein-coding RNAs infecting their hosts autonomously and in combination with a helper virus, respectively. The full-length sequence of FHVd-LR variants was determined by RT-PCR, cloning and sequencing. Despite a low global sequence identity with known viroids and Vd-LsatRNAs, FHVd-LR contains a hammerhead ribozyme (HRz) in each polarity strand. Northern blot hybridization assays identified the circular and the linear forms of both polarity strands of FHVd-LR and showed that one strand, assigned the (+) polarity, accumulates at higher levels than the (-) polarity strand in vivo. The (+) polarity RNA assumes a rod-like secondary structure of minimal free energy with the conserved domains of the HRzs located in opposition to each other, a feature typical of several viroids and viroid-like RNAs. The HRzs of both FHVd-LR polarity strands were shown to be active in vitro during transcription, self-cleaving the RNAs at the predicted sites. These data, together with the sequence variability observed in the cloned and sequenced full-length variants, indicate that FHVd-LR is a novel viroid or VdL-satRNA. According to HTS data, the coexistence of FHVd-LR of different sizes in the same host cannot be excluded. The relationships of the FHVd-LR with previously reported viroids and Vd-LsatRNAs, and the need to perform bioassays to conclusively clarify the biological nature of this circular RNA are discussed.